Additive effects of climate change on connectivity between marine protected areas and larval supply to fished areas. Issue 2 (19th September 2014) - Andrello, Marco; Mouillot, David; Somot, Samuel; Thuiller, Wilfried; Manel, Stéphanie; Bode, Michael
Abstract Aim To study the combined effects of climate change on connectivity between marine protected areas (MPAs) and larval supply to the continental shelf. Location The Mediterranean Sea, where sea surface temperatures are expected to strongly increase by the end of the 21st century, represents an archetypal situation with a dense MPA network but resource overexploitation outside. Methods Using an individual‐based mechanistic model of larval transport, forced with an emission‐driven regional climate change scenario for the Mediterranean Sea, we explored the combined effects of changes in hydrodynamics, adult reproductive timing and larval dispersal on the connectivity among MPAs and their ability to seed fished areas with larvae. Results We show that, over the period 1970–2099, larval dispersal distances would decrease by 10%, the continental shelf area seeded with larvae would decrease by 3% and the larval retention fraction would increase by 5%, resulting in higher concentration of larvae in smaller areas of the continental shelf. However, connectance within the MPA network would increase by 5% as more northern MPAs would become suitable for reproduction with increasing temperatures. We also show that the effects of changes in adult reproductive timing and larval dispersal on connectivity patterns are additive. Main conclusions Climate change will influence connectivity and the effectiveness of MPA networks, and should receive more attention in future conservation planning and large‐scale population dynamics.